Development of Interactive Media on The Root Material of Numerical Nonlinear Equations Using Geogebra and Ethercalc - Cahya Kamila Maulida; R. Ati Sukmawati; Mitra Pramita (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
This study aims to develop web-based interactive learning media by utilizing geogebra and ethercalc on the topic of determining the roots of non-linear equations numerically and evaluating their validity through material and media validity tests. The development method used is Research and Development (R&D) with the limited ADDIE development model. The data was collected through material and media validation sheets filled out by two experts. The results of the data analysis show that interactive web-based learning media for the topic of roots of nonlinear equations are developed with technologies such as HTML, CSS, Bootstrap, JavaScript, JQuery, Geogebra, Ethercalc, MathJax, Firebase, Figma, Adobe Illustrator, Canva, CapCut, and Netlify. The results of the material validity reached 84% with a high level of validity, while the media validity was 82% with a fairly high level of validity. There are several suggestions from media and material validators, namely improving the instructions for carrying out exercises and evaluations. With these results, after being repaired the learning media is ready to be tested.